2005
DOI: 10.1152/jn.00527.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating the Effects of Gravity When Intercepting Moving Objects: Differentiating Up and Down Based on Nonvisual Cues

Abstract: McIntyre. Anticipating the effects of gravity when intercepting moving objects: differentiating up and down based on nonvisual cues. J Neurophysiol 94: [4471][4472][4473][4474][4475][4476][4477][4478][4479][4480] 2005. First published August 24, 2005; doi:10.1152/jn.00527.2005. Intercepting an object requires a precise estimate of its time of arrival at the interception point (time to contact or "TTC"). It has been proposed that knowledge about gravitational acceleration can be combined with first-order, visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
103
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 42 publications
(48 reference statements)
17
103
2
Order By: Relevance
“…This conclusion is in line with previous observations on the interception of targets moving along different orientations (Senot et al 2005). This previous study found that the interception timing for targets accelerating downwards was systematically anticipated relative to when the same targets accelerated upwards.…”
Section: Vertical Versus Horizontal: Accelerated Self-motionsupporting
confidence: 93%
See 4 more Smart Citations
“…This conclusion is in line with previous observations on the interception of targets moving along different orientations (Senot et al 2005). This previous study found that the interception timing for targets accelerating downwards was systematically anticipated relative to when the same targets accelerated upwards.…”
Section: Vertical Versus Horizontal: Accelerated Self-motionsupporting
confidence: 93%
“…However, this difference was not detected in a previous study comparing upward and downward constant speed object motion (Senot et al 2005) with participants in a fixed reference frame aligned with the Earth's vertical and the virtual vertical of the visual stimulation rotating accordingly with conditions as in the present experiment. Senot et al (2005) found an anticipated (delayed) response during the downward (upward) motion only when varying the position of the head coherently with the condition (heading upward/downward), that is, adding the effect of gravity on vestibular and proprioceptive signal (De Saedeleer et al 2013). In our study, we aimed to obtain an equivalent effect by adding realism to the scene.…”
Section: Vertical Versus Horizontal: Accelerated Self-motioncontrasting
confidence: 88%
See 3 more Smart Citations